Poverty Reduction Without Economic Growth ? : Explaining Brazil's Poverty Dynamics, 1985-2004 - Ferreira, Francisco H. G. (The World Bank, 2007)
Brazil's slow pace of poverty reduction over the last two decades reflects both low growth and a low growth elasticity of poverty reduction. Using GDP data disaggregated by state and sector for a twenty-year period, this paper finds considerable variation in the poverty-reducing effectiveness of growth-across sectors, across space, and over time. Growth in the services sector was substantially more poverty-reducing than was growth in either agriculture or industry. Growth in industry had very different effects on poverty across different states and its impact varied with initial conditions related to human development and worker empowerment. The determinants of poverty reduction changed around 1994: positive growth rates and a greater (absolute) elasticity with respect to agricultural growth contributed to faster poverty reduction. But because there was so little of it, economic growth played a relatively small role in accounting for Brazil's poverty reduction between 1985 and 2004. The taming of hyperinflation (in 1994) and substantial expansions in social security and social assistance transfers, beginning in 1988, accounted for a larger share of the overall reduction in poverty